Participation of Mothers in the Care of Premature Infants and its Associated Factors - Sharare Zabihi Afroozi; Seyedeh Noshaz Mirhaghjou; Sedigheh Pakseresht; Ehsan Kazem Nejad Leili; Zahiruddin Quazi Syed (Guilan University of Medical Sciences, 2017)
Introduction: Parental participation in the care of and support to premature infants is the main factor in accelerating health improvement and growth of infants in the neonatal unit. Many factors are associated with this participation, whose investigation provides appropriate contexts for parental participation. Objective: The aim of this study was to determine the participation of mothers in the care of premature infants and factors associated with it. Material and Methods: This is a cross-sectional descriptive–analytical study in which 170 mothers with premature infants, admitted to the neonatal ward of the hospitals chosen by the Guilan University of Medical Sciences, were examined using available sampling method. The information collection tool was a questionnaire of two parts: the questionnaire of the participation of parents with hospitalized infants and the researcher-made questionnaire of the factors associated with mothers participation in the care of premature infants. After sampling, the data were statistically analyzed using descriptive and inferential statistics (t–independent, ANOVA, Pearson and Spearman correlation coefficient, and regression models). Results: The results suggest that the participation rate of mothers in infant care is 79.03%, and the birth weight (ß = -0.001, P = 0.017), gender (ß = 0.830, P = 0.024), to become familiar with the physical environment by the nurse (ß = 1.506, P = 0.001), to become familiar with the equipment used for infants in the department by the nurse (ß = 1.152, P = 0.009), explanation by a nurse for the measurements done for the infant and the reasons (ß = 0.818, P = 0.023), and blood sampling or venipuncture or pricking the infant (ß = 0.185, P = 0.041), were considered among the predictors of mothers participation. Conclusion: Due to the identification of factors associated with the participation of mothers in the care of premature infants, it is recommended that the managers and nurses use the results to improve and strengthen the participation of mothers in the care of hospitalized infants.